Acute Type A Aortic Dissection and Late Pregnancy: What Should We Do? - Liu,Lingchao (2022)
ABSTRACT Introduction: Acute type A aortic dissection (AAAD) in late pregnancy is a rare but severe disease. Lack of clinical experience is the main cause of high mortality. This study tries to investigate the multidisciplinary therapeutic strategy for these patients. Case presentation: We reported three patients with AAAD in late pregnancy. Sudden chest pain was the main clinical symptom before operation. All three patients and their newborns survived through multidisciplinary approach in diagnosis and treatment. No serious complications occurred during the mid-term follow-up. Conclusion: Multidisciplinary diagnosis and treatment strategy play a crucial role in saving the lives of pregnant women with AAAD.